2013
DOI: 10.1111/jsap.12161
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and histological correlation in diagnosing feline and canine mediastinal masses

Abstract: Cytological examination of canine and feline mediastinal masses is a relatively easy, low-cost procedure, with good agreement with final histological diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
12
0
2
Order By: Relevance
“…Typical histological appearance of thymoma reveals oval, or spindle-shaped thymic epithelial cells and mature lymphocytes to various extents. However, histology and cytology may not always correlate, with only 28% of cases being definitively confirmed on cytology in a study by Zizt and others, although a recent study found better correlation with 12 out of 17 feline thymomas confirmed on cytology and histology, and the remaining five cases confirmed on histopathology were suspected cytologically in four incidences, but were hindered by sample quality (Pintore and others 2014). HS and thymic epithelial neoplasms may occasionally share similar cytological features, with spindle and discrete cells seen in both forms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical histological appearance of thymoma reveals oval, or spindle-shaped thymic epithelial cells and mature lymphocytes to various extents. However, histology and cytology may not always correlate, with only 28% of cases being definitively confirmed on cytology in a study by Zizt and others, although a recent study found better correlation with 12 out of 17 feline thymomas confirmed on cytology and histology, and the remaining five cases confirmed on histopathology were suspected cytologically in four incidences, but were hindered by sample quality (Pintore and others 2014). HS and thymic epithelial neoplasms may occasionally share similar cytological features, with spindle and discrete cells seen in both forms.…”
Section: Discussionmentioning
confidence: 99%
“…However, neoplasms are more commonly reported and include heart base tumours (eg, chemodectoma), lymphoma, thymoma and, rarely, sarcomas, ectopic thyroid tissue and HS (Zitz and others 2008, Pintore and others 2014). …”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such lesions are commonly investigated via radiography, ultrasonography, and computer tomography (CT). All these techniques can be helpful to define the volume of the mass and the possible heterogeneity of its structure (1,3), but they are also helpful to guide sampling procedures (fine needle aspirate cytology, FNAC), thus facilitating the investigation of its cellular origin.…”
Section: Introductionmentioning
confidence: 99%
“…A final diagnosis can be reached by cytological or histological examination, but in some cases, it may be challenging and may require further ancillary techniques. Cytology may sometimes be inconclusive because of the poor quality of samples (1) or because both lymphomas and thymomas can be composed by small/medium sized lymphocytes with minimal morphological atypia (4,5). Thus, histopathology of tissue biopsy is often required for a definitive diagnosis.…”
Section: Introductionmentioning
confidence: 99%